Preparation method of material TiO2 / Fe4N / C for preparing ammonia through photocatalytic nitrate reduction

Through the preparation method of TiO2/Fe4N/C of the ammonia-made material for photocatalytic nitrate reduction, the problems of high energy consumption and environmental pollution of Haber-Bosch method are solved, and low-energy consumption, efficient ammonia production and green and environmentally friendly nitrate removal effects are achieved.

CN119488930APending Publication Date: 2025-02-21HANGZHOU NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411630953.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Existing ammonia production methods such as the Haber-Bosch method require high temperature and high pressure, resulting in high energy consumption and high CO2 emissions. At the same time, nitrate pollution in fertilizer runoff and industrial wastewater is severe, affecting the environment and human health.

Method used

The preparation method of TiO2/Fe4N/C for ammonia preparation material for photocatalytic nitrate reduction is adopted. By synthesizing oxide/nitride/carbon composite catalysts with multi-layer core-shell structures, photocatalytic nitrate reduction is used to reduce energy consumption and the environment. pollute.

Benefits of technology

It realizes low-energy consumption and efficient ammonia production, reduces CO2 emissions and nitrate pollution, and provides a green and environmentally friendly alternative ammonia production method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488930A_ABST
    Figure CN119488930A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photocatalysis, and discloses a preparation method of an ammonia preparation material TiO2 / Fe4N / C. The preparation method comprises the following steps: S1, preparing an MFN precursor; the specific method comprises the following steps: adding FeCl2. 4H2O and MoCl5 into deionized water according to a certain proportion, then adding nitrilotriacetic acid and isopropyl alcohol (IPA), stirring until the nitrilotriacetic acid and the isopropyl alcohol are completely dissolved, transferring into a reaction kettle, keeping in an oven at 150-200 DEG C for 4-8 hours, then alternately and repeatedly washing a sample with distilled water and ethanol, and then drying at 50-80 DEG C for 6-24 hours to finally obtain a MoO2 / Fe4N / C (MFC) precursor, and S2, preparing the Fe4N / C hollow sphere. The TiO2 / Fe4N / C material synthesized by the preparation method of the material TiO2 / Fe4N / C for preparing the ammonia through photocatalytic nitrate reduction is used for preparing the ammonia through reduction, different from a traditional Have-Bosch method for synthesizing ammonia, the method is used for preparing the ammonia through photocatalytic nitrate reduction, and the method has the advantages of being simple in synthesis method, convenient to operate, good in light stability, environmentally friendly and excellent in photocatalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photocatalytic technology, and in particular to a photocatalytic nitrate reduction ammonia production material TiO 2 / Fe 4 Preparation method of N / C. Background Art

[0002] Photocatalytic reduction of ammonia has received widespread attention as a popular method for synthesizing ammonia. In traditional research, the main method for preparing ammonia is the Haber-Bosch method. However, the reaction conditions of this method are very harsh (20MPa, 400℃), and a large amount of energy is consumed during the synthesis process. Photocatalysis can convert the abundant sunlight in nature into electrical energy or chemical energy, thereby promoting the progress of chemical reactions. It has the advantages of being cheap and environmentally friendly, and therefore has attracted much attention.

[0003] In today's era, ammonia is an irreplaceable chemical raw material in human production and life, and is also the most promising energy transportation carrier. Ammonia is the main component of nitrogen fertilizer and is also widely used in the manufacture of plastics, pharmaceuticals, explosives, synthetic fibers and resins, as well as industrial chemical products such as printing and dyeing. However, most of the world's ammonia supply currently relies on the Haber-Bosch process, which requires high temperatures of 350 to 550°C and high pressures of 15 to 25 MPa to drive, releasing up to 300 million tons of CO2 into the atmosphere each year. On the other hand, the accumulation of nitrate (NO3-) in groundwater and surface water caused by fertilizer runoff and industrial wastewater poses a serious threat to the environment and human health. Chemical (electrodialysis, ion exchange, etc.) and biological (denitrification) methods involve a large amount of wastewater and energy consumption. Therefore, there is an urgent need to develop a low-energy, efficient and easy-to-implement nitrate removal method. The nitrate photocatalytic conversion strategy to ammonia is not only expected to solve the problem of nitrate accumulation in the environment, but also provides an alternative method for ammonia production. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the shortcomings of the prior art, the present invention provides a photocatalytic nitrate reduction ammonia production material TiO 2 / Fe 4 The preparation method of N / C has the advantages of simple synthesis method, convenient operation, good photostability, green environmental protection and excellent photocatalytic performance. It solves the problem that most of the ammonia supply in the world currently relies on the Haber-Bosch process (which requires high temperature of 350-550°C and high pressure of 15-25MPa to drive, and releases up to 300 million tons of CO into the atmosphere every year). 2) and fertilizer runoff and industrial wastewater cause the accumulation of nitrate (NO3-) in groundwater and surface water, posing a serious threat to the environment and human health. Chemical (electrodialysis, ion exchange, etc.) and biological (denitrification) methods involve large amounts of wastewater and energy consumption.

[0006] (II) Technical solution

[0007] In order to achieve the purpose of the above-mentioned synthesis method being simple, easy to operate, having good photostability, being green and environmentally friendly, and having excellent photocatalytic performance, the present invention provides the following technical scheme: a photocatalytic nitrate reduction ammonia production material TiO 2 / Fe 4 The preparation method of N / C comprises the following steps:

[0008] Step S1: preparing MFN precursor; the specific method is:

[0009] FeCl 2 ·4H 2 O and MoCl 5 Add to deionized water in a certain proportion, then add nitrilotriacetic acid and isopropyl alcohol (IPA) and stir until completely dissolved, then transfer to a reactor, keep in an oven at 150-200°C for 4-8 hours, then wash the sample repeatedly with distilled water and ethanol, then dry at 50-80°C for 6-24 hours, and finally, obtain MoO 2 / Fe 4 N / C (MFC) precursor;

[0010] Step S2: Preparation of Fe 4 N / C hollow ball; the specific method is:

[0011] The prepared MFC precursor was calcined in an Ar atmosphere quartz tube furnace at 500-600°C for 2 hours, and a black solid was collected. Then, it was etched with potassium hydroxide solution for 18-36 hours, and then washed with deionized water until neutral. Finally, it was dried in a vacuum environment at 40-80°C for 6-12 hours to obtain Fe 4 N / C hollow ball;

[0012] Step S3: Preparation of TiO 2 Precursor; the specific method is:

[0013] Concentrated HNO 3 Slowly drip into HPLC grade ethanol, then add tetrabutyl titanate solution and stir for 2 minutes (Note: In order to prevent the hydrolysis of tetrabutyl titanate, the prepared mixture needs to be used within 1 hour) to obtain TiO 2 Precursor;

[0014] Step S4: Preparation of TiO 2 / Fe 4N / C; The specific method is:

[0015] The Fe 4 The N / C hollow spheres and the titanium dioxide precursor were mixed in a certain proportion and added to a long-necked flask, and then stirred in a water bath at 15-25°C for 12-24 hours. After the stirring, the solvent was evaporated at room temperature, and then aged in a sand bath at 50-100°C for 1 hour to obtain TiO 2 / Fe 4 N / C.

[0016] Preferably, the FeCl in step S1 2 ·4H 2 O and MoCl 5 The molar ratio is between 1:1 and 1:3.

[0017] Preferably, the concentration of the potassium hydroxide solution in step S2 is 1 to 15 mol / L.

[0018] Preferably, the concentrated HNO in step S3 3 The volume ratio of HPLC grade ethanol is between 1:50 and 1:100.

[0019] Preferably, the Fe in step S4 4 The molar ratio of the N / C hollow spheres to the titanium dioxide precursor is between 1:0.3 and 1:3.

[0020] (III) Beneficial effects

[0021] Compared with the prior art, the present invention provides a photocatalytic nitrate reduction ammonia production material TiO 2 / Fe 4 The preparation method of N / C has the following beneficial effects:

[0022] 1. The photocatalytic nitrate reduction ammonia material TiO 2 / Fe 4 Preparation method of N / C, by synthesizing TiO 2 / Fe 4 The use of N / C materials to produce ammonia by reduction is different from the traditional Haber-Bosch method for synthesizing ammonia. It uses photocatalytic nitrate reduction to produce ammonia. It has the characteristics of high catalytic efficiency, mild operating conditions and environmental protection.

[0023] 2. The photocatalytic nitrate reduction ammonia material TiO 2 / Fe 4 Preparation method of N / C based on Fe 4 N antiperovskite crystal structure, and designed a carbon-shell-encapsulated Fe 4N composite structure, and then through the serial route of disproportionation, nitridation and carbonization reactions, a multilayer core-shell structured oxide / nitride / carbon composite catalyst (TiO2 / Fe 4 N / C), titanium dioxide is excited by light to generate photogenerated carriers, which are then transferred to Fe through the carbon shell. 4 N active sites for nitrate reduction reaction, among which 4.2% TiO 2 / Fe 4 N / C exhibited the best photocatalytic performance in the photocatalytic nitrate reduction reaction to produce ammonia. 2 ) irradiation, the NH4+ generation rate was 79.45mmol / gcat. / h, and the selectivity of nitrate reduction to ammonia reached 89.12%; under visible light irradiation, the NH4+ generation rate was 46.87mmol / gcat. / h, and the selectivity of nitrate reduction to ammonia reached 87.10%. 2 / Fe 4 The photocatalytic activity of N / C composites depends largely on the filled titanium dioxide, which produces a large number of photogenerated carriers and significantly improves the photocatalytic nitrate reduction efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Transmission electron microscope (TEM) and scanning electron microscope (SEM) images of the relevant materials prepared for the present invention;

[0025] Figure 2 The TiO prepared in the present invention 2 / Fe 4 N / C high-resolution data images;

[0026] Figure 3 (a) XRD diagram of MFC prepared in the present invention before and after etching and (b) XRD diagram after filling with titanium dioxide;

[0027] Figure 4 The 4.2% TiO prepared in this invention 2 / Fe 4 XPS peak spectrum of N / C;

[0028] Figure 5 (a) MFC and TiO 2 / Fe 4 UV-Vis curves of N / C series catalysts (b) Band gap diagram;

[0029] Figure 6 The TiO 2 / Fe 4 Photocurrent response diagram of N / C series catalysts;

[0030] Figure 7 The TiO prepared in the present invention 2 / Fe 4 N / C series catalyst performance diagram;

[0031] Figure 8 The Fe 4 Schematic diagram of the dosage of N / C hollow spheres and the volume of titanium dioxide precursor. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] See also Figure 1-8 , a photocatalytic nitrate reduction material TiO 2 / Fe 4 Preparation method of N / C.

[0034] Embodiment 1:

[0035] Step S1: FeCl 2 ·4H 2 O and MoCl 5 Add to deionized water in a molar ratio of 1:1 to 1:3, then add nitrilotriacetic acid and isopropyl alcohol (IPA) and stir until completely dissolved, then transfer to a reactor, keep in an oven at 150 to 200 ° C for 4 to 8 hours, then wash the sample repeatedly with distilled water and ethanol, then dry at 50 to 80 ° C for 6 to 24 hours, and finally, obtain MoO 2 / TiO 2 / Fe 4 N / C (MFC) precursor;

[0036] Step S2: The prepared MFC precursor was calcined in an Ar atmosphere quartz tube furnace at 500-600°C for 2 hours, and a black solid was collected. Then, it was etched with a potassium hydroxide solution for 18-36 hours, and then washed with deionized water until neutral. Finally, it was dried in a vacuum environment at 40-80°C for 6-12 hours to obtain Fe 4 N / C hollow ball;

[0037] Step S3: Concentrated HNO 3 Slowly drip into HPLC grade ethanol, then add tetrabutyl titanate solution and stir for 2 minutes (Note: In order to prevent the hydrolysis of tetrabutyl titanate, the prepared mixture needs to be used within 1 hour) to obtain TiO 2 Precursor;

[0038] Step S4: The Fe 4 The N / C hollow spheres and the titanium dioxide precursor were mixed in a molar ratio of 1:0.3 to 1:1.2 and added to a long-necked flask, and then stirred in a water bath at 15 to 25°C for 12 to 24 hours. After the stirring, the solvent was evaporated at room temperature, and then aged in a sand bath at 50 to 100°C for 1 hour to obtain 2.1 to 3.0% TiO 2 / Fe 4 N / C.

[0039] Embodiment 2:

[0040] Step S1: FeCl 2 ·4H 2 O and MoCl 5 Add to deionized water in a molar ratio of 1:1 to 1:3, then add nitrilotriacetic acid and isopropyl alcohol (IPA) and stir until completely dissolved, then transfer to a reactor, keep in an oven at 150 to 200 ° C for 4 to 8 hours, then wash the sample repeatedly with distilled water and ethanol, then dry at 50 to 80 ° C for 6 to 24 hours, and finally, obtain MoO 2 / Fe 4 N / C (MFC) precursor;

[0041] Step S2: The prepared MFC precursor was calcined in an Ar atmosphere quartz tube furnace at 500-600°C for 2 hours, and a black solid was collected. Then, it was etched with a potassium hydroxide solution for 18-36 hours, and then washed with deionized water until neutral. Finally, it was dried in a vacuum environment at 40-80°C for 6-12 hours to obtain Fe 4 N / C hollow ball;

[0042] Step S3: Concentrated HNO 3 Slowly drip into HPLC grade ethanol, then add tetrabutyl titanate solution and stir for 2 minutes (Note: In order to prevent the hydrolysis of tetrabutyl titanate, the prepared mixture needs to be used within 1 hour) to obtain TiO 2 Precursor;

[0043] Step S4: The Fe 4 The N / C hollow spheres and the titanium dioxide precursor were mixed in a molar ratio of 1:0.5 to 1:1.5 and added to a long-necked flask, and then stirred in a water bath at 15 to 25°C for 12 to 24 hours. After the stirring, the solvent was evaporated at room temperature, and then aged in a sand bath at 50 to 100°C for 1 hour to obtain 3.1 to 4.0% TiO 2 / Fe 4 N / C.

[0044] Embodiment three:

[0045] Step S1: FeCl 2 ·4H 2 O and MoCl 5 Add to deionized water in a molar ratio of 1:1 to 1:3, then add nitrilotriacetic acid and isopropyl alcohol (IPA) and stir until completely dissolved, then transfer to a reactor, keep in an oven at 150 to 200 ° C for 4 to 8 hours, then wash the sample repeatedly with distilled water and ethanol, then dry at 50 to 80 ° C for 6 to 24 hours, and finally, obtain MoO 2 / Fe 4 N / C (MFC) precursor;

[0046] Step S2: The prepared MFC precursor was calcined in an Ar atmosphere quartz tube furnace at 500-600°C for 2 hours, and a black solid was collected. Then, it was etched with a potassium hydroxide solution for 18-36 hours, and then washed with deionized water until neutral. Finally, it was dried in a vacuum environment at 40-80°C for 6-12 hours to obtain Fe 4 N / C hollow ball;

[0047] Step S3: Concentrated HNO 3 Slowly drip into HPLC grade ethanol, then add tetrabutyl titanate solution and stir for 2 minutes (Note: In order to prevent the hydrolysis of tetrabutyl titanate, the prepared mixture needs to be used within 1 hour) to obtain TiO 2 Precursor;

[0048] Step S4: The Fe 4 The N / C hollow spheres and the titanium dioxide precursor were mixed in a molar ratio of 1:0.8 to 1:2 and added to a long-necked flask, and then stirred in a water bath at 15 to 25°C for 12 to 24 hours. After the stirring, the solvent was evaporated at room temperature, and then aged in a sand bath at 50 to 100°C for 1 hour to obtain 4.1 to 5.0% TiO 2 / Fe 4 N / C.

[0049] Embodiment 4

[0050] Step S1: FeCl 2 ·4H 2 O and MoCl 5 Add to deionized water in a molar ratio of 1:1 to 1:3, then add nitrilotriacetic acid and isopropyl alcohol (IPA) and stir until completely dissolved, then transfer to a reactor, keep in an oven at 150 to 200 ° C for 4 to 8 hours, then wash the sample repeatedly with distilled water and ethanol, then dry at 50 to 80 ° C for 6 to 24 hours, and finally, obtain MoO 2 / Fe 4N / C (MFC) precursor;

[0051] Step S2: The prepared MFC precursor was calcined in an Ar atmosphere quartz tube furnace at 500-600°C for 2 hours, and a black solid was collected. Then, it was etched with a potassium hydroxide solution for 18-36 hours, and then washed with deionized water until neutral. Finally, it was dried in a vacuum environment at 40-80°C for 6-12 hours to obtain Fe 4 N / C hollow ball;

[0052] Step S3: Concentrated HNO 3 Slowly drip into HPLC grade ethanol, then add tetrabutyl titanate solution and stir for 2 minutes (Note: In order to prevent the hydrolysis of tetrabutyl titanate, the prepared mixture needs to be used within 1 hour) to obtain TiO 2 Precursor;

[0053] Step S4: The Fe 4 The N / C hollow spheres and the titanium dioxide precursor were mixed in a molar ratio of 1:1 to 1:3 and added to a long-necked flask, and then stirred in a water bath at 15 to 25°C for 12 to 24 hours. After the stirring, the solvent was evaporated at room temperature, and then aged in a sand bath at 50 to 100°C for 1 hour to obtain 5.1 to 6.0% TiO 2 / Fe 4 N / C.

[0054] In the case implementation, transmission electron microscopy (TEM) and scanning electron microscopy (SEM) were first used to characterize the morphology and structure of the material, such as Figure 1 Figure a shows MoO 2 / Fe 4 TEM image of N / C (MFC) material. It can be observed from the figure that the synthesized MFC presents a regular spherical structure. Figure 1 Middle b is the TEM image of MFC after being etched by potassium hydroxide solution. Figure 1 In middle a, the color becomes lighter in the center of the image, showing the MoO inside the MFC sphere. 2 The product Fe 4 N / C, Figure 1 c, d are TEM and SEM images of titanium dioxide filled after etching. Figure 1 In middle c, it can be observed that the color of the image taken of the nanospheres becomes darker, which means that titanium dioxide is filled into the hollow spheres after etching.

[0055] In the case implementation, Figure 2 As can be seen in b, the lattice fringes of 0.37 nm correspond to the carbon shell. Figure 2 The 0.219 nm lattice fringe in c corresponds to Fe 4 The (111) crystal plane of N, Figure 2 The 0.34 nm lattice fringe in middle d corresponds to the TiO 2 The (101) crystal plane of the two components is interlaced, indicating that Fe 4 N and TiO 2 The two are mixed together.

[0056] In the case implementation, XRD was used to characterize the phase and structure information of the catalyst. Figure 3 Figure a shows the XRD patterns of MFC before and after being etched by potassium hydroxide. It can be seen from the figure that the hollow sphere Fe 4 N / C preserves good Fe 4 N structure, antiperovskite Fe 4 The (100), (110) and (111) planes of N (PDF77-2006) correspond to three diffraction peaks at 24.7°, 33.5° and 42.8°, respectively. Figure 3 The XRD pattern after filling with titanium dioxide is shown in b. It can be seen from the figure that the components of the catalyst include TiO 2 and Fe 4 N.

[0057] In the case implementation, XPS was used to characterize the surface elemental composition and chemical valence state of the catalyst. Figure 2 It can be seen that TiO 2 / Fe 4 N / C mainly contains C, N, O, Fe and Ti elements. Figure 4 a is 4.2% TiO 2 / Fe 4 Detailed peak separation of O1s XPS corresponding to N / C, where 531.6eV is attributed to the Ti-O bond and 529.7eV is due to the presence of oxygen vacancies. Figure 4 In b, the binding energy of Ti 2p spectrum is mainly at 458.3eV and 464.0eV, which are attributed to Ti4+-2p3 / 2 and Ti4+-2p1 / 2, respectively, which means the presence of titanium dioxide in the prepared catalyst. Figure 4 In c, the XPS spectrum of Fe2p shows multiple valence states of Fe in the catalyst, where the peaks with binding energies of 706.4 eV and 719.2 eV belong to Fe0, and the peaks with binding energies of 711.9 eV and 723.9 eV are attributed to Fe3+. It is worth noting that Fe0 and Fe3+ correspond to Fe 4 Fe-Fe and Fe-N components in N, Figure 4 The XPS spectrum of N1s in the d-N matrix has only one peak at 400.8 eV, which corresponds to the Fe-N bond. 4 The presence of N, the above data proves from the side that TiO 2Filled with Fe 4 N / C hollow ball.

[0058] In the case implementation, optical properties are crucial to catalysts. This patent uses Uv-vis spectroscopy to test the light absorption properties of materials. Figure 5 As can be seen from a in the figure, the curve of MFC tends to be a straight line with no obvious absorption peak, which means that there are no atoms or functional groups that can be excited in MFC. After etching and filling with titanium dioxide, the catalyst has a clear absorption peak at 300-400nm, indicating that its light absorption capacity in the ultraviolet and visible range has been improved, which means that the prepared catalyst can achieve photocatalytic nitrate reduction. Figure 5 As shown in b, this is the result of calculating the bandgap width of the absorption curve using the Tauc-Plot method. This patent found that 4.2% TiO 2 / Fe 4 The band gaps of N / C and pure TiO2 are approximately 2.22eV and 3.24eV, respectively. These data reveal that compared with pure TiO 2 , 4.2% TiO 2 / Fe 4 The bandgap of N / C is significantly reduced, which effectively enhances the photon excitation of the catalyst.

[0059] In the case implementation, extending the lifetime of photogenerated carriers is crucial, so this patent uses transient photocurrent to evaluate the photoelectric properties of the material during the research process. Figure 6 As can be seen from the figure, all samples were subjected to on / off cycling experiments under UV irradiation to observe the photocurrent intensity. The results show that 4.2% TiO 2 / Fe 4 The maximum instantaneous photocurrent of N / C reached 0.1μA / cm 2 , which means that when the content of titanium dioxide is 4.2%, the catalyst has the best catalytic performance.

[0060] In the case implementation, by contrast, 4.2% TiO 2 / Fe 4 N / C exhibited the best photocatalytic nitrate reduction performance under various light sources, such as Figure 7 As shown in a and b, under ultraviolet light (100mW / cm2), the NH4+ generation rate is 79.45mmol / gcat. / h, and the selectivity of nitrate reduction to ammonia reaches 89.12%; under visible light irradiation, the NH4+ generation rate is 46.87mmol / gcat. / h, and the selectivity of nitrate reduction to ammonia reaches 87.10%. Figure 7As shown in c, this article further tested the catalyst stability, and the catalyst also showed good stability.

[0061] In the case implementation, the Fe 4 N / C hollow spheres and titanium dioxide precursor are mixed in a certain proportion and added into a long-necked flask, such as Figure 7 As shown, the mixture was then stirred in a water bath at 18°C ​​for 20 hours. After the stirring was completed, the solvent was evaporated at room temperature, followed by aging in a sand bath at 80°C for 1 hour.

[0062] In summary, the photocatalytic nitrate reduction ammonia production material TiO 2 / Fe 4 Preparation method of N / C synthesized TiO 2 / Fe 4 The use of N / C materials to produce ammonia by reduction is different from the traditional Haber-Bosch method for synthesizing ammonia. This method utilizes photocatalytic nitrate reduction to produce ammonia, and has the advantages of simple synthesis method, convenient operation, good photostability, green environmental protection and excellent photocatalytic performance.

[0063] In addition, the multilayer core-shell structured oxide / nitride / carbon composite catalyst (TiO2 / Fe4N / C) was synthesized via a series of disproportionation, nitridation, and carbonization reactions. Titanium dioxide was photoexcited to generate photogenerated carriers, which were then transferred to Fe through the carbon shell. 4 N active sites for nitrate reduction reaction, among which 4.2% TiO 2 / Fe 4 N / C exhibits the best photocatalytic performance in the photocatalytic nitrate reduction to ammonia reaction. Under ultraviolet light (100mW / cm2), the NH4+ generation rate is 79.45mmol / gcat. / h, and the selectivity of nitrate reduction to ammonia is 89.12%; under visible light irradiation, the NH4+ generation rate is 46.87mmol / gcat. / h, and the selectivity of nitrate reduction to ammonia is 87.10%. 2 / Fe 4 The photocatalytic activity of N / C composites depends largely on the filled titanium dioxide, which produces a large number of photogenerated carriers, significantly improving the efficiency of photocatalytic nitrate reduction, solving the problem that most of the world's ammonia supply currently relies on the Haber-Bosch process (which requires high temperatures of 350-550°C and high pressures of 15-25MPa to drive, releasing up to 300 million tons of CO into the atmosphere each year). 2 ) and fertilizer runoff and industrial wastewater cause the accumulation of nitrate (NO3-) in groundwater and surface water, posing a serious threat to the environment and human health. Chemical (electrodialysis, ion exchange, etc.) and biological (denitrification) methods involve large amounts of wastewater and energy consumption.

[0064] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0065] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a photocatalytic nitrate reduction ammonia production material TiO2 / Fe4N / C, characterized in that: The following steps are involved: Step S1: preparing MFN precursor; The specific method is: FeCl2·4H2O and MoCl5 are added to deionized water in a certain proportion, and then nitrilotriacetic acid and isopropyl alcohol (IPA) are added and stirred until completely dissolved, and then transferred to a reactor, kept in an oven at 150-200°C for 4-8 hours, and then the sample is repeatedly washed with distilled water and ethanol alternately, and then dried at 50-80°C for 6-24 hours, and finally, a MoO2 / Fe4N / C (MFC) precursor is obtained; Step S2: preparing Fe4N / C hollow spheres; the specific method is: The prepared MFC precursor was calcined in an Ar atmosphere quartz tube furnace at 500-600°C for 2 hours, and a black solid was collected, which was then etched with a potassium hydroxide solution for 18-36 hours, then washed with deionized water until neutral, and finally dried in a vacuum environment at 40-80°C for 6-12 hours to obtain Fe4N / C hollow spheres; Step S3: preparing TiO2 precursor; the specific method is: Slowly drip concentrated HNO3 into HPLC grade ethanol, then add tetrabutyl titanate solution and stir for 2 minutes (Note: in order to prevent hydrolysis of tetrabutyl titanate, the prepared mixed solution needs to be used within 1 hour) to obtain TiO2 precursor; Step S4: preparing TiO2 / Fe4N / C; the specific method is: The Fe4N / C hollow spheres obtained by etching previously and the titanium dioxide precursor are mixed in a certain proportion and added to a long-necked flask, and then stirred in a water bath at 15-25°C for 12-24 hours. After stirring, the solvent is evaporated at room temperature, and then aged in a sand bath at 50-100°C for 1 hour to obtain TiO2 / Fe4N / C.

2. The method for preparing the photocatalytic nitrate reduction ammonia production material TiO2 / Fe4N / C according to claim 1, characterized in that: In step S1, the molar ratio of FeCl2·4H2O to MoCl5 is between 1:1 and 1:

3.

3. The method for preparing the photocatalytic nitrate reduction ammonia production material TiO2 / Fe4N / C according to claim 1, characterized in that: The concentration of the potassium hydroxide solution in step S2 is 1 to 15 mol / L.

4. The method for preparing the photocatalytic nitrate reduction ammonia production material TiO2 / Fe4N / C according to claim 1, characterized in that: The volume ratio of concentrated HNO3 to HPLC grade ethanol in step S3 is between 1:50 and 1:

100.

5. The method for preparing the photocatalytic nitrate reduction ammonia production material TiO2 / Fe4N / C according to claim 1, characterized in that: In step S4, the molar ratio of the Fe4N / C hollow spheres to the titanium dioxide precursor is between 1:0.3 and 1:3.